English Language Acquisition: A Literature Review of Recent Research Trends and Learning Processes - Suhria Suhria; Uswatun Hasanah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Dampal Selatan, 2026)
This study aimed to identify research trends, learning processes, and factors influencing English Language Acquisition (ELA) based on Scopus-indexed publications from 2021 to 2026. A literature review method was employed using articles retrieved from the Scopus database with the keyword “English Language Acquisition.” The search was limited to journal articles, open-access publications, and studies published between 2021 and 2026. A total of 17 articles that met the inclusion criteria were analyzed through thematic analysis. The findings revealed five major themes: phonological acquisition, morphosyntactic acquisition, vocabulary development, cognitive factors, and instructional interventions. Phonological acquisition emerged as the most dominant area, emphasizing the influence of first-language systems on second-language speech perception and production. The review also demonstrated that cognitive factors, including memory and auditory processing abilities, significantly contribute to language learning outcomes. Furthermore, multimodal learning environments and technology-supported instruction were found to facilitate language development. Overall, the findings indicate that English language acquisition is a multidimensional process shaped by the interaction of linguistic, cognitive, perceptual, and environmental factors.